Achieving Sustained Virological Response in Liver Transplant Recipients With Hepatitis C Decreases Risk of Decline in Renal Function. Issue 8 (24th August 2018) - Satapathy, Sanjaya K.; Joglekar, Kiran; Molnar, Miklos Z.; Ali, Bilal; Gonzalez, Humberto C.; Vanatta, Jason M.; Eason, James D.; Nair, Satheesh P.
Abstract : The effect of antiviral therapy (AVT) on kidney function in liver transplantation (LT) recipients has not been well described despite known association of hepatitis C virus (HCV) infection with chronic kidney disease (CKD). We compared the incidence of CKD and end‐stage renal disease (ESRD) in 204 LT recipients with HCV based on treatment response to AVT. The mean estimated glomerular filtration rate (eGFR) at baseline (3 months after LT) was similar in the sustained virological response (SVR; n = 145) and non‐SVR group (n = 59; 69 ± 21 versus 65 ± 33 mL/minute/1.73 m 2 ; P  = 0.27). In the unadjusted Cox proportional regression analysis, the presence of SVR was associated with an 88% lower risk of CKD (hazard ratio, 0.12; 95% confidence interval [CI], 0.05‐0.31) and 86% lower risk of ESRD (odds ratio, 0.14; 95% CI, 0.05‐0.35). Similar results were found after adjusting for propensity score and time‐dependent Cox regression analyses. The estimated slopes of eGFR based on a 2‐stage mixed model of eGFR were calculated. Patients with SVR had a less steep slope in eGFR (–0.60 mL/minute/1.73 m 2 /year; 95% CI, –1.50 to 0.30; P = 0.190) than recipients without SVR (–2.53 mL/minute/1.73 m 2 /year; 95% CI, –3.99 to –1.07; P = 0.001), and the differences in the slopes were statistically significant ( P = 0.026). In conclusion, in LT recipients with chronic HCV infection, achieving SVR significantly lowers the risk of decline in renal function and progression to ESRD independent of the AVT therapy used.